Vibrational Spectroscopic Study Of 4-Aminopyrimidine Complexes - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2009)
A series of Hofmann-type 4-aminopyrimidine complexes with the general formula M(4APM)(2)M'(CN)(4) (where M = Mn, Zn or Cd; M'= Pd or Pt; 4APM = 4-aminopyrimidine) have been prepared for the first time and their FT-IR (4000-400 cm(-1)) and FT-Raman (4000-50 cm-1) spectra measured. 4APM is coordinated to M(II) through one of the pyrimidine ring nitrogen atoms as a monodentate ligand: the exo-cyclic nitrogen is not involved in the complex formation. Vibrational bands arising from both 4APM and the M'(CN)(4) group were assigned. Comparison of the low frequency vibrational wavenumbers of the tetracyanometallate sheets of the isostructural compounds allow a tentative assignment for nu(M'-C), delta(M'C = N), pi(M'C N), delta(CM'C), nu(M-N)(4APM), nu(M-NC) and delta(NMN)(4APM) vibrations. The coordination effect on 4APM vibrational wavenumbers is analysed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Aminopyrimidine; Hofmann-type Complexes; Infrared and Raman Spectra; Tetracyanoplatinate; Tetracyanopalladate; Molecules; Behavior; Polymer; Hofmann-tipi kompleksler; Moleküller; Davranış; Polimer